Peningkatan Kemampuan Menulis Ayat-Ayat Al-Qur’an Melalui Metode Follow The Line - Husnan Sulaiman; Siti Julaeha (STAI Al-Musaddadiyah Garut, 2026)
This study focuses on improving the ability to write the verses of the Qur'an through the Follow the Line method in the subject of Al-Qur'an Hadith phase D at MTs Cokroaminoto Karangtengah Garut. The ability to write the Qur'an is one of the Arabic language skills that is highly demanded for students to master. However, students in phase D in class VIII-B MTs Cokroaminoto Karangtengah still have low writing skills. The results of pre-research observations showed that students who already have the ability to write the Qur'an were only around 40% of the total 33 students. The purpose of this study is to describe the use of the Follow the Line Method in improving students' writing skills. This research method is Classroom Action Research (CAR). Data collection is carried out through tests, observations, and interviews. The CAR data analysis technique only uses simple statistical formulas to calculate the average value and percentage of students' ability to write the verses of the Qur'an. Based on the results of classroom action research conducted in two cycles, students' ability to write verses of the Qur'an increased to 60% in the first cycle and to 40% in the second cycle. This shows that students' ability to write verses of the Qur'an increased by 20% from the pre-cycle to the first cycle and 80% in the second cycle. So, over all there is an increase in students' ability to write verses of the Qur'an with a significance of 40% from the pre-cycle to cycle II. Keywords: ability to write verses of the Qur'an, follow the line method